Importance of clinical history in the diagnosis of psittacosis: A case report. (October 2022) - Khadka, Sulochana; Timilsina, Bibek; Pangeni, Raju Prasad; Regmi, Pradeep Raj; Thapa, Anupam Singh
Abstract: Introduction: Psittacosis, caused by the bacteria Chlamydia psittaci, is primarily a disease of birds that can be transmitted to humans. The clinical manifestations of the disease are wide, ranging from asymptomatic illness to fulminant psittacosis with multi-organ failure. The organism gets attached to the upper respiratory mucosa after inhalation and the majority remain asymptomatic. However, some people may develop symptoms of atypical pneumonia. Case presentation: Psittacosis usually presents with sudden onset fever with chills and rigor, headache, and myalgia. Here we present a case of a 35 years old female with a history of close contact with parrots who presented to the ER with complaints of high-grade fever and headache for 2 weeks which started 2 days after her parrots died. Discussion: The disease usually manifests as flu-like symptoms or pneumonia and is included in the differential diagnosis of community-acquired pneumonia. Investigations reveal neutrophilia, raised erythrocyte sedimentation rate, C-reactive protein, and elevated liver enzymes which were consistent with the findings of our patient. Chest X-ray showed ill-defined consolidation in the right middle and lower lobes which were inconclusive. Hence, a CT chest was done which revealed patchy ground glass opacities with surrounding consolidation giving a reverse halo sign. Due to her contact with birds and CT findings which were suggestive of psittacosis, she was started on doxycycline and her condition improved thereafter. Conclusion: We highlight the importance of proper history taking and awareness on zoonotic diseases to the general public to prevent, diagnose and treat the disease effectively. Highlights: The clinical manifestations of the disease are wide, ranging from asymptomatic illness to fulminant psittacosis with multi organ failure. It is important to take proper history regarding exposure to reservoir animals and birds by the doctors to diagnose and treat the disease effectively. Awareness on zoonotic diseases to the general public is important to prevent the disease occurrence.